(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The emergence of artificial intelligence (AI) has significantly transformed the field of photojournalism, introducing both groundbreaking opportunities and complex ethical challenges. This article explores how AI technologies are reshaping the creation, curation, verification, and dissemination of photographic content in journalism. Drawing on interdisciplinary perspectives from media studies, AI ethics, and journalism practice, the discussion critically examines the dual nature of AI’s influence: its potential to enhance journalistic efficiency and creativity, and its capacity to erode public trust and manipulate visual reality. The analysis concludes that the future of photojournalism will depend on the responsible integration of AI, sustained ethical oversight, and renewed commitments to journalistic integrity and truthfulness in visual storytelling.